Avaliação do crescimento muscular e reprodutivo modulado pelo fotoperíodo da tilápia-do-nilo (Oreochromis niloticus) durante todo o ciclo produtivo - Santos, Márcia Dantas dos (2022)
This work is structured in two chapters: 1) It is elaborated it in the format of a review article, with topics related to Aquaculture and physiology of teleosts, with emphasis on Nile tilapia. 2) It refers to the study, in an intensive culture system, of the performance of tilapia submitted to different photoperiods, during 6 months (180 days). It addresses the objectives, methodology and presentation and discussion of the results. The objectives were: to identify the patterns of somatic growth, muscle growth, energy mobilization and reproduction of tilapia throughout 180 days submitted to different photoperiods. For this purpose, we set up a recirculation system with 9 water tanks (1000L each), with 3 tanks each photoperiod (T1=24Light:0Dark; T2=18L:06D and T3=12D:12D). We stocked embryos in incubators, then in hatchery, and finally in water tanks (n=142 animals/each). The tilapia presented varied performances depending on the biometric variables and photoperiods. Mortality was considerable in the first 15 days of live with significant mortality up to 30 days with significant differences (p<0.0001 and p<0.0001, respectively). The lowest mortality results were identified at T1. As for body mass, significant differences (p<0.004) were recorded on day 135, with T1 showing higher body mass (56.57±23.11g). Regarding the total length, there were significant differences between treatments on days 135(p<0.002) and 180(p<0.016) post-hatching. T1 showed the greatest lengths (14.85±2.58 and 19.52±2.99cm) on both days, respectively. Regarding mass gain, specific growth rate and condition factor, there were no statistical differences between treatments. The skeletal muscle growth showed a tendency pattern of increasing fiber length over the of days, especially at T1, characterizing a predominantly hypertrophic growth. The animals developed, in all treatments, fibers >180μm, that started to be identified from day 90. The hepatic glycogen showed significant differences as an function of photoperiods on days 60, 90, 120 and 150((p<0.002; 0.047; 0.001 and 0.001, respectively) with increased deposition frequency for T1. As for lipid stocks, there was a statistical difference on days 150 and 180 (p<0.001 and 0.003, respectively) between treatments. T3 obtained a higher frequency of hepatic accumulation. Regarding sex determination, a percentage of sex inversion was identified: 85.7% of the phenotypic males and 14.3% for intersex males for all treatments. There was no potentiation of the hormone, in the sexual inversion, by the photoperiod. On day 90, the tilapia showed germ cells in an undifferentiated phase and spermatogonia. In this sense, we describe the data from day 120 onwards. The fishes were in maturation stage, because they presented the highest percentages of spermcysts at day 150 (T1-26%, T2-53% and T3-37%) with the lowest percentage for T1. On day 180, spermatozoa showed lower rates compared to the previous collection (T1-23%, T2-27% and T3-32%). On this last day, it is possible to suggest, by the decreasing data, that the animals could be entering the regression phase. The present study revealed that the T1 photoperiod provided better results in the rearing of Nile tilapia, regarding the productive performance. As for reproduction, T1 showed lower percentages of maturation.